The Influence of Brand Image and Lifestyle on Purchase Decisions of Vespa Piagio Motorcycles in the City of Mataram: Pengaruh Brand Image dan Gaya Hidup terhadap Keputusan Pembelian Sepeda Motor Vespa Piaggio di Kota Mataram - Muhammad Nauval Daffa Din Hadi; Rusminah Rusminah; Hilmiati Hilmiati (Institut Studi Islam Sunan Doe, 2023)
This study aims to determine the significance of the influence of Brand Image and Livestyle on purchasing decisions of Vespa Piaggio motorcycles in Mataram City. The type of research used is quantitative research with an associative approach, taking a sample of 48 respondents which are people who have purchased a vespa matic piaggio in the city of Mataram. The results showed that the brand image variable had a positive and significant effect on purchasing decisions. This is indicated by the t-value of the brand image variable (X1) 2.367 which is greater than the t-table value of 2,014. Likewise, the livestyle variable has a positive and significant effect on purchasing decisions, with the t-value of the lifestyle variable (X2) 3.288, which is greater than the t-table value in 2,014.